META ANALYSIS OF THE EFFECT OF STUDENT WORKSHEET USE ON STUDENT LEARNING OUTCOMES - Indri Yulia Putri; Desnita Desnita; Amali Putra; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2022)
This research is a meta-analysis of the effect ofStudent Worksheets on student learning outcomes. Thereal conditions found in the field of physics studentlearning outcomes are still low. To improve studentlearning outcomes, teaching materials are needed thatcan attract students' interest in learning, one of which isStudent Worksheets. This study aims to analyze theeffect of Student Worksheets on student learningoutcomes. The research method used in this research ismeta-analysis research. By collecting and summarizingseveral articles. Where the sample used consists of 30articles that have been published in various nationaland international journals. The selected articles arearticles that can be processed to calculate the effect sizeon the use of Student Worksheets which are thengrouped into four indicators, namely based on educationlevel, grade level, learning model and research area.First, the use of Student Worksheets has a significanteffect on indicators for junior high school educationwith a summary effect size of 1,041 in the high category.Second, the use of Student Worksheets has a significantimpact in class VIII with a summary effect size of 1,205which is categorized as very high. Third, the use ofworksheets has a significant effect on the ContextualTeaching and Le&